An Initial Study in the Development of International Postgraduate Students Academic Stress Scale (IPSASS) - Lumban Gaol, Nasib Tua; Lin, Jhy-Sheng (COUNS-EDU: The International Journal of Counseling and Education, 2017)
The aim of this study is to develop a new scale, the International Postgraduate Students Academic Stress Scale (IPSASS), for measuring the sources of academic stress on international postgraduate students. A 79-item prototype was developed by reviewing literatures and conducting interviews. Exploratory Factor Analysis (EFA) was used to investigate the contribution of each item and the number of factor in the IPSASS. The result of study revealed that IPSASS has seven subscales including: (1) Learning Process, (2) Time Management, (3) Financial Problems, (4) Relationship’s Building, (5) Supervision, (6) Acquiring Resources, and (7) Academic Performance. The IPSASS is a reliable and valid instrument for measuring the source and level of academic stress on international postgraduate students. This study has contribution significantly to the literature and practice for providing a valuable understanding regarding psychological and academic issues faced by international postgraduate students.